Prevalence and seasonal variation of precipitants of heart failure hospitalization and risk of readmission. (1st October 2020) - Wang, Nelson; Farrell, Maura; Hales, Susan; Hanvey, Kelly; Robertson, Gina; Sharp, Precilla; Tofler, Geoffrey
Abstract: Aims: To determine the prevalence and seasonal variation in precipitants of heart failure (HF) hospitalization and the risk of subsequent HF hospitalizations. Methods: We analysed the characteristics and outcomes of patients hospitalized with HF and enrolled in the Management of Cardiac Failure program in Sydney, Australia. Potential precipitants of HF hospitalization were identified, and Cox-regression analyses performed according to the precipitant. Results: Among 6918 patients hospitalized with HF, 5384 (78%) had identified one or more precipitating factors leading to the hospitalization and 3648 (53%) had a single identifiable precipitant. Most precipitants were due to one or more of five prespecified causes - infection (n = 2014), ischemia (n = 1781), arrhythmia (n = 1724), medication related (n = 925) and diet non-compliance (n = 408). All precipitants were more common during winter (p < 0.001), especially infection related precipitants, of which 36% occurred during winter. Among patients with a single identifiable precipitant, one-year risk for HF readmission was lower when the precipitant was arrhythmia (16%) or infection (17%) than when the precipitant was ischemia (21%), dietary non-compliance (23%) or medication related (25%). The precipitant for HF rehospitalizations were more likely to be the same precipitant for the initial admission: infection vs no infection (HR 1.51, 95% CI 1.08–2.13), ischemia vs no ischemia (HR 2.79, 95% CI 1.83–4.25), arrhythmia vs no arrhythmia (HR 3.31, 95% CI 1.87–5.88) and medication related vs not medication related (HR 2.28, 95% CI 1.39–3.74). Conclusion: The precipitant of HF hospitalization influences the risk and precipitant of subsequent HF hospitalizations. Identifying and targeting interventions towards the precipitating factor may be an important strategy to prevent future HF hospitalizations. Highlights: Patients hospitalized with worsening HF are at high risk of rehospitalization. Most HF hospitalizations can be attributed to one of five precipitants. Patients with arrhythmia related precipitants are at lower risk of all-cause mortality. Patients are more likely to have a HF rehospitalization for the same precipitant of the initial admission.